An Electronic Task Management (ETM) system for after hours hospital work and subsequent socially mediated effects of task completion. (September 2016) - Marshall, Stuart; Warren, Benjamin; Roodenburg, Owen; Smolenaers, Frank; Leon, Graciela; McKimm, Amy; Keogh, Martin; Stuart, Josh; Logan, Maria; Stripp, Andrew
Modern Hospitals are under ever increasing efficiency pressures; patient safety and flow are paramount. In the after-hours period, many tasks such as transfers between clinical areas and procedures are delayed because the resources may be limited or poorly distributed compared to in hours. An Electronic Task Management (ETM) system was iteratively designed to support the redesign of the after hours staffing and task distribution model that addressed these delays and improved staff efficiency. The solution consisted of a task controller program installed on desktop PCs in the clinical areas and similar software on smart phones for the clinical staff (operatives) undertaking the clinical tasks. In a system without clinical leadership and workload transparency, the forced reallocation of tasks to operatives was strongly resisted by the operatives. The development of an interface that allowed workloads of all operatives to be visualized by all other operatives led to a socially mediated, cooperative solution that was readily accepted. The quality of the information sent by the ETM was superior to the previous paging system and workloads were more equitable among operatives with the introduction of the ETM.